2009
DOI: 10.1021/la803050r
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Quantification of Oxygen Species Adsorbed on Pt(111) Single-Crystal and Polycrystalline Pt Electrodes by Photoelectron Spectroscopy

Abstract: We have positively identified oxygen species on Pt(111) single-crystal and polycrystalline Pt electrodes in N2-purged 0.1 M HF solution by X-ray photoelectron spectroscopy combined with an electrochemical cell. Four oxygen species (Oad, OHad, and two types of water molecules) were distinguished. The binding energies of each species were nearly constant over the whole potential region and independent of the single- or polycrystalline electrodes. The coverages, however, varied considerably and were dependent on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

33
192
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(227 citation statements)
references
References 26 publications
33
192
2
Order By: Relevance
“…In recent years, it has become well-established that platinum electrodes immersed in acidic or basic aqueous electrolytes react with water when the potential is increased from the edge of the hydrogen under potential deposition potential region,~0.35 V on the reversible hydrogen electrode scale, which will be used in this paper, to around 0.6 V. At 0.6 V, water begins to be oxidized to OH(ads), and at around 0.8 V OH(ads), it begins to be oxidized to O(ads) [1][2][3]. Even before the careful work in these recent references, it was well-known that water oxidizes on platinum cathodes in acid or base as the potential is increased out of the double-layer region, beginning around 0.6 V. It has been long assumed that these adsorbates control the kinetics and current densities of oxygen cathodes by blocking active adsorption sites for O 2 .…”
Section: Volcano Plots and Electrode Surface Site Blockingmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, it has become well-established that platinum electrodes immersed in acidic or basic aqueous electrolytes react with water when the potential is increased from the edge of the hydrogen under potential deposition potential region,~0.35 V on the reversible hydrogen electrode scale, which will be used in this paper, to around 0.6 V. At 0.6 V, water begins to be oxidized to OH(ads), and at around 0.8 V OH(ads), it begins to be oxidized to O(ads) [1][2][3]. Even before the careful work in these recent references, it was well-known that water oxidizes on platinum cathodes in acid or base as the potential is increased out of the double-layer region, beginning around 0.6 V. It has been long assumed that these adsorbates control the kinetics and current densities of oxygen cathodes by blocking active adsorption sites for O 2 .…”
Section: Volcano Plots and Electrode Surface Site Blockingmentioning
confidence: 99%
“…The first showed that both OH and H 2 O bond more weakly to the (111) Pt skin on Pt 3 Cr alloy surfaces, but the weakening was greater for OH, and from this, it was deduced that the shift of the reversible potential for reducing OH(ads) to H 2 O(l) would be about 110 mV positive [7]. The implication was that the skin surface would be clear of OH(ads) at 110 mV higher potential than on pure Pt(111).…”
Section: Volcano Plots and Electrode Surface Site Blockingmentioning
confidence: 99%
“…The application of vibrational spectroscopy is also limited by the strong absorbance of both the electrolyte solution and the electrolyte membrane, which makes the weak vibrational signature of the OH species virtually undetectable 13,14 . X-ray photoelectron spectroscopy (XPS), which probes all oxygenated surface species with equal sensitivity, has been used to study Pt single-crystal electrodes 15,16 in ultra-high vacuum. The challenge with these ex situ measurements is to minimize decomposition and contamination during sample transfer, as surface water species on Pt all desorb above 200 K in ultra-high vacuum 17 .…”
mentioning
confidence: 99%
“…[1][2][3][4] For PEFC anode and cathode catalysts, the activity and its degradation have been analyzed by multilateral techniques such as X-ray photoelectron spectroscopy combined with an electrochemical cell (EC-XPS), 2,[5][6][7][8] in situ Fourier-transform infrared spectroscopy (FTIR), [9][10][11][12][13][14][15][16][17][18][19][20][21][22] electrochemical quartz crystal microbalance (EQCM), [23][24][25][26] in situ scanning tunneling microscopy (STM), [27][28][29][30][31] in addition to conventional electrochemical measurements such as rotating disk electrode (RDE), [32][33][34] channel flow electrode (CFE), 21,35,36 and channel flow double electrode (CFDE) methods. [37][38][39][40][41][42] Based on these results, new practical catalysts have been synthesized.…”
Section: Introductionmentioning
confidence: 99%